Reasons for student enrollment in nursing studies - Čukljek, Snježana (Array, 2020)
The aim of the research was to determine the reasons for students enrolling in nursing studies, priorities in the choice of studies and differences in the reasons and priorities for choosing enrollment with regard to previously completed high school. The research was conducted on full-time nursing students of the University of Applied Health Sciences who enrolled in the first year of study in the academic year 2017/2018 and 2018/2019. For the purpose of the research, an anonymous questionnaire was used. The questionnaire includes questions related to demographic data and questions about the reasons related to enrollment in nursing studies, whether any of their family members or friends work in the health care system and whether any of the members of their family is a health worker. Students were required to rank their choice of the study of nursing on a scale of 1 to 10 at the time of enrollment. Students who have previously completed high school for nurses most often stated the expansion of existing knowledge, the acquisition of new knowledge, and the continuation of previous education as the reasons for enrolling in nursing studies. Students who have completed other types of high schools stated interest in medicine, nursing, health, helping others, good employment opportunities, and nursing being interesting as reasons for enrollment. Participants in this research significantly more often stated that their family members do not work in the health care system. When enrolling in the study, the majority of the students’ first choice was the study of nursing at the higher education institution where the research was conducted – in the 2017 74.7% of participants, and in 2018 67.3% of participants. There is no statistically significant difference in the average ranking of the choice of the nursing study with respect to the year of enrollment (p=0.692).